Evaluation of High School Curriculum in Forming Student Character in the Digital Era - Simbolon, Sri Nur Inayah; Khaerani HARAHAP; Syafnan (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This study analyzes the evaluation of high school curriculum in shaping students' character in the digital era, focusing on the Independent Curriculum. Character education is the main pillar in shaping a generation that is intelligent, moral, and spiritual. The Independent Curriculum emphasizes flexibility, differentiation, and the formation of the Pancasila Student Profile, but its implementation faces challenges such as teacher readiness and facilities. The digital era brings positive and negative impacts, such as easy access to information as well as the risk of individualism and the spread of negative content, which complicates character formation. The evaluation shows the importance of the role of teachers, the school environment, and families in supporting character education. A character strengthening strategy is needed that integrates moral values ​​and digital literacy in learning, supported by teacher training, adequate infrastructure, and assessment system reform. The goal is to create high school graduates with strong, resilient, and capable characters to face global challenges.